1988
DOI: 10.1093/jaoac/71.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Zeranol/Zearalenone and Their Metabolites in Edible Animal Tissue by Liquid Chromatography with Electrochemical Detection and Confirmation by Gas Chromatography/Mass Spectrometry

Abstract: A sensitive method is described for the determination and confirmation of zeranol and zearalenone, as well as their isomers and metabolites, in edible animal tissue. The analytes are extracted from tissue with methanol, hydrolyzed enzymatically, cleaned up by acidbase partitioning, determined by liquid chromatography (LC) with electrochemical (EC) detection, and confirmed by gas chromatography/ mass spectrometry (GC/MS). LC analysis is performed by isocratic elution with a buffered mobile phase using a Nova-Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In addition, compared with other analytical methods, LC‐based methods often offer the advantage of simpler sample preparation, with a reduction in time‐consuming and sometimes error‐prone derivatisation steps as in GC/MS. In the case of Zs, ultraviolet (UV) absorbance detection has been used routinely, but few studies have been reported using electrochemical (EC) detection 16, 17. The screen‐printed technology used in EC detection is very attractive because it is inexpensive and disposable 18.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compared with other analytical methods, LC‐based methods often offer the advantage of simpler sample preparation, with a reduction in time‐consuming and sometimes error‐prone derivatisation steps as in GC/MS. In the case of Zs, ultraviolet (UV) absorbance detection has been used routinely, but few studies have been reported using electrochemical (EC) detection 16, 17. The screen‐printed technology used in EC detection is very attractive because it is inexpensive and disposable 18.…”
Section: Introductionmentioning
confidence: 99%
“…Zeranol antibody was diluted to a suitable working titre with 50 mmol l 21 TRIS-HCl buffer, pH 7.75, containing 0.9% NaCl, 0.5% BSA, 0.05% NaN 3 , 0.01% Tween 40, 0.05% bovine gglobulin, 20 mM diethylenetriaminepentaacetic acid and 20 mg ml 21 Cherry Red. A 50 ml volume of the solution was incubated in goat anti-rabbit IgG-coated microtitration wells for 2 h at room temperature and the wells were washed four times with wash solution.…”
Section: Preparation Of Dry Chemistry Microtitre Platesmentioning
confidence: 99%
“…A bovine urine sample (250 ml) was added to 750 ml of phosphate buffer (0.5 mol l 21 , pH 7.4) and incubated overnight at room temperature, or for 2 h at 37 °C, with 10 ml of bglucuronidase from Escherichia coli (Roche Diagnostics, Lewes, East Sussex, UK). Zeranol IAC columns were preconditioned with 4 ml each of 0.5 mol l 21 NaCl, 80% v/v ethanol and de-ionised water. Deconjugated sample was applied to the column under gravity.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Various analytical techniques have been developed for screening and confirmative determination of Z and metabolic analogs. In addition to the abovementioned ELISA [19,20] and GC [21,22], thin-layer chromatography (TLC) [23], and high performance liquid chromatography (HPLC) with UV [24,25] and mass spectrometry [26][27][28] detections have also been reported. Both ELISA and TLC are cost-effective methods suitable for larger scale initial sample screening, but neither provides enough selectivity to differentiae among Z analogues [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, GC and LC based analysis in combination with mass spectrometry have been used to provide sensitivity and confirmation of residual Zs, however the high maintenance and cost have prevented them from being a routine practice. Consequently, HPLC with UV detection is still the most common combination currently employed in the determination of Zs residuals in food or tissue [24,25], very few studies were done using electrochemical (EC) detector [22,29]. In 2008, an EC method with carbon nanotube-modified glassy carbon electrode was reported to determine Zs in urine [30], more recently, dual detection of Zs in moldy rice, soybean and cornflakes using series connection of UV and EC detectors was reported [31].…”
Section: Introductionmentioning
confidence: 99%